2020
DOI: 10.1080/10705511.2020.1779069
|View full text |Cite
|
Sign up to set email alerts
|

Sample Size Recommendations for Continuous-Time Models: Compensating Shorter Time Series with Larger Numbers of Persons and Vice Versa

Abstract: Autoregressive modeling has traditionally been concerned with time-series data from one unit (N = 1). For short time series (T < 50), estimation performance problems are well studied and documented. Fortunately, in psychological and social science research, besides T, another source of information is often available for model estimation, that is, the persons (N > 1). In this work, we illustrate the N/T compensation effect: With an increasing number of persons N at constant T, the model estimation performance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 31 publications
0
35
2
Order By: Relevance
“…For study planning, other criteria might be of interest as well. For instance, Hecht and Zitzmann (2021) illustrated the dependence of model performance (an aggregated measure consisting of convergence, bias, and coverage) on number of persons N and time points T. So even if a sufficient statistical power is achieved with some N and T, model performance might still be suboptimal.…”
Section: Discussionmentioning
confidence: 99%
“…For study planning, other criteria might be of interest as well. For instance, Hecht and Zitzmann (2021) illustrated the dependence of model performance (an aggregated measure consisting of convergence, bias, and coverage) on number of persons N and time points T. So even if a sufficient statistical power is achieved with some N and T, model performance might still be suboptimal.…”
Section: Discussionmentioning
confidence: 99%
“…Another issue concerns the small T situation in the presence of multiple subjects. On the one hand, multiple subjects can be an additional source of information for model estimation and can compensate for small T to some degree (Hecht and Zitzmann 2020 ). On the other hand, boundary effects may occur (i.e., the first and the last couple of rows in a fully embedded time series may exhibit bias that does not cancel, especially with short time series and large embedding dimensions; Boker et al 2018 ) and add up.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the sample size also matters for CTMs. A simulation study by Hecht and Zitzmann (2020) indicated that for a design like ours with five measurement occasions, 250 to 500 people are needed to obtain reliable estimates. Thus, our sample size was sufficient to compute CTMs.…”
Section: Assumptions Preconditions and Required Sample Sizes Of Continuous Time Modelsmentioning
confidence: 91%